PRINCIPLES AND CASE STUDIES OF AN ISLAMIC APPROACH FOR SCIENCE EDUCATION - Mabrouk, Ahmed Hassan (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2025)
The way of teaching science in Western schools has become the main channel for developing secular minds. Due to the strong technological and economic impact of science in today’s world, teaching science through a religion-averse approach would be a successful recipe for developing a secular society. Islamization efforts aimed at deprogramming the secular orientation in science teaching and restoring the compatible position of science with the Islamic world view. In continuation of such efforts, this article is written for Muslim scientists and educators who aspire to align science presentation with their faith. The article discusses ten aspects to be mended in the current practices of science teaching. Each aspect is presented through an Islamic principle, supplemented with a few case studies. Science presentation through an Islamic lens is meant to elevate science from a collection of dry, technical points to a discipline that arouses our sense of appreciation of the wisdom and perfection in our world. As such, this article could serve as a link between the general principles of Islamization of knowledge on one hand and the teaching approaches of science on the other hand. Similar efforts of Christian scientists are also surveyed. At last, recommendations for building a conducive environment for an Islamic-friendly presentation of science are given.